Low literacy levels likely to impede rural women’s successbin business - Guloba, Madina; Ssewanyana, Sarah; Birabwa, Elizabeth (Economic Policy Research Centre, 2017)
Being literate is a prerequisite in business management and sustainability. While evidence shows that Uganda’s entrepreneurial potential is high globally, female entrepreneurs were still being presented with limited opportunities to expand their business and few tried to increase or independently manage their enterprises. Education levels for women especially in rural areas and among the youth is still low and hence most likely to miss out of government programmes that aim to uplift their livelihoods such as those targeting income enhancement amidst agricultural shortfalls. Programmes must offer mixed approaches in enterprise business chain and emphasis on adult literacy programmes along entrepreneurship is vital for rural business sustainability.